Co‐Culture System of Human Enteroids/Colonoids with Innate Immune Cells. (9th November 2020) - Staab, Janet F.; Lemme‐Dumit, Jose M.; Latanich, Rachel; Pasetti, Marcella F.; Zachos, Nicholas C.
Abstract: Human intestinal enteroids derived from adult stem cells offer a relevant ex vivo system to study biological processes of the human gut. They recreate cellular and functional features of the intestinal epithelium of the small intestine (enteroids) or colon (colonoids) albeit limited by the lack of associated cell types that help maintain tissue homeostasis and respond to external challenges. In the gut, innate immune cells interact with the epithelium, support barrier function, and deploy effector functions. We have established a co‐culture system of enteroid/colonoid monolayers and underlying macrophages and polymorphonuclear neutrophils to recapitulate the cellular framework of the human intestinal epithelial niche. Enteroids are generated from biopsies or resected tissue from any segment of the human gut and maintained in long‐term cultures as three‐dimensional structures through supplementation of stem cell growth factors. Immune cells are isolated from fresh human whole blood or frozen peripheral blood mononuclear cells (PBMC). Monocytes from PBMC are differentiated into macrophages by cytokine stimulation prior to co‐culture. The methods are divided into the two main components of the model: (1) generating enteroid/colonoid monolayers and isolating immune cells and (2) assembly of enteroid/colonoid‐immune cell co‐cultures with separate apical and basolateral compartments. Co‐cultures containing macrophages can be maintained for 48 hr while those involving neutrophils, due to their shorter life span, remain viable for 4 hr. Enteroid‐immune co‐cultures enable multiple outcome measures, including transepithelial resistance, production of cytokines/chemokines, phenotypic analysis of immune cells, tissue immunofluorescence imaging, protein or mRNA expression, antigen or microbe uptake, and other cellular functions. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Seeding enteroid fragments onto Transwells for monolayer formation Alternate Protocol : Seeding enteroid fragments for monolayer formation using trituration Basic Protocol 2 : Isolation of monocytes and derivation of immune cells from human peripheral blood Basic Protocol 3 : Isolation of neutrophils from human peripheral blood Basic Protocol 4 : Assembly of enteroid/macrophage or enteroid/neutrophil co‐culture